An approach to anisocoria. Issue 6 (November 2016) - Gross, Jordan R.; McClelland, Collin M.; Lee, Michael S.
Abstract : Purpose of review: Anisocoria is a finding seen on a daily basis in nearly every eye clinic. Although often benign, it can also represent the sole sign of a life-threatening disease making an up-to-date understanding of pathophysiology and diagnosis essential for anyone practicing medicine. Recent findings: Many aspects of the traditional approach to anisocoria still hold true today, but advancements in imaging technology and changing trends in pharmacologic diagnosis and localization have led many to rethink that approach. In addition, the differential diagnosis for anisocoria continuously expands with identification and improved understanding of causal disease processes. Summary: The present article discusses an approach to the classic anisocoria diagnostic algorithm modified by current knowledge from the most recent literature.